F. Botton Beja (2019). Ensayos sobre China. Una antología. México: El Colegio de México. 378 pp. - Villagrán, Ignacio (Estudios de Asia y África, 2020)
F. Botton Beja (2019). Ensayos sobre China. Una antología. México: El Colegio de México. 378 pp.